Balancing Parental and Child Interests in Research Subject Compensation - Appel, J. M. (Journal of bioethical inquiry, 2025)
Both minors enrolled in human subject research and their parents often receive compensation for the former's participation. While considerable literature addresses the ethics of such compensation, the existing literature does not yet consider the challenge of minors and parents who may have divergent views regarding how such compensation should be expended. Since parents generally have broad legal authority over both monetary and in-kind compensation received by their children, ensuring that compensation earmarked for minor subjects are actually expended in accordance with the subjects' interests may prove challenging. This paper assesses the existing legal and ethical landscape in this area and proposes several potential mechanisms through which researchers and IRBs might address this largely overlooked dilemma.